The effects of using pictures on EFL learners’ vocabulary retention - Đào Ra Ta Na (Trường Đại học Trà Vinh, 2023)
The current study is carried out to achieve two research objectives. The first objective is to find out the attitude of a group of seventh-graders towards using pictures to learn vocabulary in their English classes. The second objective is to examine the impact of using pictures on vocabulary learning among this group of EFL learners.